(untitled) (Eureka Journal of Humanities and Social Research, 2026)
Hormone therapy is widely used in the management of endocrine disorders, reproductive health conditions, and gender-affirming care. However, conventional hormone therapy protocols are often standardized and may not adequately account for inter-individual variability in genetics, metabolism, lifestyle, and treatment response. Artificial intelligence (AI) offers a promising approach to developing personalized hormone therapy plans by integrating large-scale patient data and advanced predictive modeling. This study explores the conceptual framework, methodological design, and potential clinical benefits of AI-driven individualized hormone therapy planning. The findings suggest that AI-based systems can improve treatment precision, reduce adverse effects, and support clinical decision-making, while also highlighting ethical and data-related challenges.